Effect of carbon dioxide pressure on 4-t-butylphenol hydrogenation activity of supported rhodium catalyst - Hiyoshi, Norihito; Sato, Osamu; Yamaguchi, Aritomo; Rode, Chandrashekhar V.; Shirai, Masayuki (Journal of the Japan Petroleum Institute, 2013)
Hydrogenation of 4-t-butylphenol over an activated carbon-supported rhodium catalyst in carbon dioxide solvent was analyzed based on phase observation with a view cell and calculations of the solubility of 4-t-butylphenol using the Peng-Robinson equation of state as a function of carbon dioxide pressure. The reaction experiments showed that the initial reaction rate of 4-t-butylphenol at 313 K under 2 MPa of hydrogen pressure was increased by the addition of carbon dioxide, especially above a total pressure of 11 MPa. Direct visual observation showed that the solubility of 4-t-butylphenol increased with higher carbon dioxide pressure. The calculations based on the Peng-Robinson equation of state also showed that the solubility of 4-t-butylphenol in the 4-t-butylphenol carbon dioxide hydrogen (2 MPa) system at 313 K significantly increased by addition of carbon dioxide above a total pressure of 11 MPa. We concluded that the increase in the hydrogenation rates was caused by the increased concentration of 4-t-butylphenol substrate in the carbon dioxide solvent.
Keywords: 4-t-Butylphenol hydrogenation; Carbon dioxide solvent; Peng-Robinson equation; Rhodium catalyst; Supercritical fluid